Chrysin, baicalein and galangin are indirect activators of the human constitutive androstane receptor (CAR). Issue 2 (4th March 2015) - Carazo Fernández, Alejandro; Smutny, Tomas; Hyrsová, Lucie; Berka, Karel; Pavek, Petr
Graphical abstract